Analysis of sleep quality and influencing factors in migraine patients with patent foramen ovale - Hu Yijun; Zhang Diwen; Wang Libo; Liu Bo; Ye Hongmei; Zhao Xiongfei (Sichuan jingshen weisheng)
BackgroundMigraine is a common chronic neurological disease， and patent foramen ovale （PFO） has been closely associated with migraine. Current research primarily focuses on the pathological mechanism and the therapeutic effects of interventional closure， with limited attention paid to the impact of PFO on sleep quality in migraine patients.ObjectiveTo compare the difference in sleep quality between PFO-positive and PFO-negative migraine patients， and to analyzes influencing factors of sleep quality in PFO-positive migraine patients， so as to provide references for clinical interventions to improve sleep quality in PFO-positive migraine patients.MethodsA total of 673 migraine patients who met the diagnostic criteria of migraine in the International Classification of Headache Disorders， third edition （ICHD-3）， and all patients underwent contrast-enhanced transcranial Doppler （c-TCD） and transthoracic echocardiographic right heart contrast echocardiography （cTTE） in the Third Hospital of Mianyang from January 2020 to October 2024. Basic demographic data were collected using a self-designed questionnaire， headache severity was assessed with the Visual Analogue Scale （VAS）， and sleep quality was invaluated using the Pittsburgh Sleep Quality Index （PSQI）. PFO patients was diagnosed through c-TCD combined with c-TTE. Binary logistic regression analysis was employed to examine the influencing factors of sleep quality in PFO-positive migraine patients.ResultsA total of 673 （100.00%） migraine patients were enrolled， including 223 PFO-positive cases （33.14%） and 450 PFO-negative cases（66.86%）. The PFO-positive group showed significantly more severe headache severity （χ2=15.799， P<0.01） and poorer sleep quality （χ2=14.377， P<0.01） compared with PFO-negative group. PFO-positive patients demonstrated significantly higher barrier factor scores of sleep quality， sleep latency， sleep efficiency， sleep disturbance， hypnotic medication use， and daytime dysfunction compared with PFO-negative counterparts （t=3.634， 3.269， 2.785， 3.428， 2.907， 3.637， Bonferroni adjust P<0.05/7=0.007）.By contrast， no significant difference was noted in sleep duration scores between the two groups（t=2.349， Bonferroni adjust P>0.05/7=0.007）.The Binary Logistic regression analysis revealed that age （OR=1.021， 95% CI： 1.001~1.041）， headache severity （OR=6.030， 95% CI： 4.085~8.901）， and PFO grade （OR=1.893，95% CI： 1.288~2.784）were significant influencing factors for sleep quality in migraine patients with PFO.ConclusionMigraine patients with PFO-positive exhibited poorer sleep quality compared wtih PFO-negative patients. Older age， higher headache servity， and more severe PFO grade are identified as risk factors for impaired sleep quality in PFO-positive migraine patients.